Entropically driven MHC class I recognition by human inhibitory receptor leukocyte Ig-like receptor B1 (LILRB1/ILT2/CD85j). - Shiroishi, M; Kuroki, K; Tsumoto, K; Yokota, A; Sasaki, T; Amano, K; Shimojima, T; Shirakihara, Y; Rasubala, L; Van Der Merwe, P; Kumagai, I; Kohda, D; et al. (2006)
The human inhibitory receptor, leukocyte immunoglobulin (Ig)-like receptor B1 (also called Ig-like transcript (ILT) 2, CD85j), is broadly expressed on leukocytes. LILRB1 binds to a wide range of major histocompatibility complex class I molecules (MHCIs) and transduces negative signals that can, for example, prevent killing of MHCI-expressing cells. Here we report the kinetic, thermodynamic, NMR and crystallographic analyses of MHCI recognition by LILRB1. Kinetic studies demonstrated that LILRB1 binds to MHCIs with fast association and dissociation rates, typical of cell-cell recognition receptors. Thermodynamic analyses showed that LILRB1-MHCI interactions are entropically driven (-TdeltaS = -9.4 approximately -6.6 kcal mol(-1)) with low heat capacity changes (deltaC(p) = -0.22 approximately -0.10 kcal mol(-1) K(-1)). The crystal structures of LILRB1 in the different crystal forms exhibited variation in the elbow angle between the two N-terminal Ig-like domains, indicating interdomain flexibility. Consistently, NMR analysis provided the direct evidence of the conformational changes of LILRB1 upon the MHCI binding. These findings suggest that LILRB1-MHCI interactions, while involving some conformational adjustment, are not accompanied by a very large reduction in conformational flexibility at the binding interface. This mode of binding is distinct from "induced-fit" binding, which is associated with large reductions in conformational flexibility, and would be suitable for rapid engagement of MHCIs to enable fast monitoring of the expression level of MHCIs on target cells.